Exploring the influence of language politeness, humor styles, and positive communication on cyberbullying among generation Z students - Pandang, Abdullah; Umar, Nur Fadhilah; Mantasiah, Mantasiah; Yusri, Yusri; Muhayyang, Maemuna; Sakkir, Geminastiti (Edelweiss Applied Science and Technology, 2025)
This study evaluates the impact of language politeness, humor styles, and positive communication on cyberbullying behavior among Generation Z, as well as the role of interpersonal skills as a moderating variable. Using a correlational quantitative design with path analysis, the research involved 389 students from South Sulawesi, West Sulawesi, and Central Sulawesi. The sample was obtained through proportional stratified random sampling and a validated questionnaire that measured language politeness, humor style, positive communication, and cyberbullying behavior. The validity and reliability of the instrument were assessed using goodness of fit indices (GFI) and confirmatory factor analysis (CFA). Data analysis included normality testing, correlation analysis, and path analysis. Findings revealed that language politeness does not directly affect cyberbullying, but humor style has a significant negative impact. Interpersonal skills mediate the relationship between language politeness, humor style, and cyberbullying. Positive communication and strong interpersonal skills can reduce the likelihood of engaging in cyberbullying behavior.